2001
DOI: 10.1080/026992001300054856
|View full text |Cite
|
Sign up to set email alerts
|

SpeakingF0characteristics of elderly Euro-American and African-American speakers: building a clinical comparative platform

Abstract: This study sought to describe speaking fundamental frequency characteristics of elderly Euro-American and African-American individuals and to explore the eOE ects of ethnicity and ageing on vocal parameters of speech production. Speech samples from 42 elderly Euro-American and 37 elderly African-American individuals (age range: 70± 80 years) were compared on measures of mean speaking fundamental frequency (F 0 ), maximum and minimum speaking F 0 , speaking F 0 standard deviation (F 0 SD), and speaking F 0 rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…A tanult genderspecifikus viselkedésmintákat, illetve szociális/szociokulturális faktorokat (Fitch-Holbrook 1970, Wheat-Hudson 1988, utóbbiakhoz kapcsolódóan a gége leszorításával elért mélyebb alaphangot a fiatal fiúknál (Huszár 2009). Továbbá az artikuláció pontosságát (Diehl et al 1996), illetve a testalkatot (Collins 2000) és a toldalékcső paramétereit (Xue et al 2001), amelyek szintén befolyásolhatják a beszédet.…”
Section: Bevezetésunclassified
“…A tanult genderspecifikus viselkedésmintákat, illetve szociális/szociokulturális faktorokat (Fitch-Holbrook 1970, Wheat-Hudson 1988, utóbbiakhoz kapcsolódóan a gége leszorításával elért mélyebb alaphangot a fiatal fiúknál (Huszár 2009). Továbbá az artikuláció pontosságát (Diehl et al 1996), illetve a testalkatot (Collins 2000) és a toldalékcső paramétereit (Xue et al 2001), amelyek szintén befolyásolhatják a beszédet.…”
Section: Bevezetésunclassified
“…F0 is affected by several factors such as anthropomorphic differences of phonatory system, ethnicity, gender, age and emotional state of speakers [24][25][26]. In addition to the physical or other functional factors, socio-cultural factors such as bilingualism may also influence pitch characteristics (F0) of sounds [27]. Altenberg and Ferrand [28] reported that the English/Russian bilinguals consistently had a higher mean F0 than the age and gender-matched peers of a monolingual Russian or English.…”
Section: Introductionmentioning
confidence: 99%